Andarilhando pelas trajetórias de formação: narrativas (auto)biográficas de pedagogas docentes universitárias - Reis, Cristiane Medianeira da Silva (2017)
This dissertation is linked to Research Line 2-School Practices and Public Policies, of the Postgraduate Program in Education of the Federal University of Santa Maria (UFSM), generated by the interest around the research to what extent the (auto)biographical narratives of the trajectories of university pedagogues professors from the courses of Pedagogy at the Federal University of Santa Maria – UFSM and from the Franciscan University Center -UNIFRA, in Santa Maria – RS, are related to their teaching practices? The unroll of this intention, specifically were: To recognize in the (auto) biographical narrative the educational elements that influenced the search for the trajectory of continuing education and allowed me to encounter with this research theme; to theorize the methodological path, with the choice of qualitative research methodology, method of (auto)biographical narratives; analyze theses themes, dissertations and articles from other researchers to think about my research path; to rescue the path taken by education in Brazil, the first professors and the arisen of the pedagogy course; to discuss the professor education in higher education; and to verify how the autobiographical narratives are possibilities of professors reflection, considering life histories and trajectory of formation, as a reflection movement for understanding the initial and continued formative processes. Lastly, I develop the research, I present the data collection, the criteria used, the interviews and the (auto)biographical narratives of the four university pedagogues professors.